Research of the investment results of pension savings - G. F. Fatkhlislamova (Управление)
This article makes a research of current trends in the investment of pension savings of citizens, transferred to the trust management of the state management company Vnesheconombank, non-state pension funds and private management companies for the period from 2005 to 2017. The dynamics of the market value of their investment portfolios have traced. The main periods of similar dynamics of the increase in the value of the analysed investment portfolios have highlighted. The main factors determining this dynamic have identified. The structure of investing pension savings by these entities in various types of assets - government and corporate securities, deposits and accounts of credit organizations has presented. The dynamics of changes in the structure of assets for the period 2005-2017, and the investment strategy of each of the subjects of investment of pension savings during the analyzed period have evaluated.The article considers the effectiveness of investing pension savings not only from the standpoint of protecting pension savings from inflationary losses, but also from the point of view of the loss-making activity of the state management company Vnesheconombank, non-state pension funds and private management companies. The data on the total amount of losses according to the results of investment for the study period have provided. The author has made conclusions about the ratio of profitability and risk of investing pension savings in various types of assets. The research revealed key trends in the development of the compulsory pension insurance system in exercising the trust management of the state management company Vneshekonombank, non-state pension funds and private management companies using pension savings of citizens over a 13-year period since the start of trust management of pension savings.